2015
DOI: 10.4049/jimmunol.1402898
|View full text |Cite
|
Sign up to set email alerts
|

IL-10 Potentiates Differentiation of Human Induced Regulatory T Cells via STAT3 and Foxo1

Abstract: Foxp3+ regulatory T cells (Tregs) play essential roles in maintaining the immune balance. Although the majority of Tregs are formed in the thymus, increasing evidence suggests that induced Tregs (iTregs) may be generated in the periphery from naive cells. However, unlike in the murine system, significant controversy exists regarding the suppressive capacity of these iTregs in humans, especially those generated in vitro in the presence of TGF-β. Although it is well known that IL-10 is an important mediator of T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
175
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 230 publications
(189 citation statements)
references
References 55 publications
5
175
2
Order By: Relevance
“…Previous reports have shown that FoxO1 and Stat3 antagonize each other in the regulation of T-cell function (34,35) and leptin signaling transduction (36,37). We were thus prompted to evaluate the role of FoxO1 during the process of β-cell EMT in this CPRD model, because the inflammatory environment in the PDL-tail presumably induces significant local cell stress.…”
Section: Resultsmentioning
confidence: 99%
“…Previous reports have shown that FoxO1 and Stat3 antagonize each other in the regulation of T-cell function (34,35) and leptin signaling transduction (36,37). We were thus prompted to evaluate the role of FoxO1 during the process of β-cell EMT in this CPRD model, because the inflammatory environment in the PDL-tail presumably induces significant local cell stress.…”
Section: Resultsmentioning
confidence: 99%
“…In the context of T helper differentiation, the T follicular helper (T FH ) subset requires engagement of the costimulatory receptor, ICOS, which activates PI3K/AKT to suppress Foxo1-dependent gene expression (Rolf et al, 2010; Stone et al, 2015). Foxo1 also plays a role in the differentiation of murine and human regulatory T cells (Tregs) (Hsu et al, 2015; Kerdiles et al, 2010); notably, Foxo1 activity must be finely tuned to preserve Treg trafficking and function (Luo et al, 2016). The decision of CD8 + T cells to adopt effector or memory gene expression programs also depends on the balance of AKT and FOXO activity (Hess Michelini et al, 2013; Macintyre et al, 2011).…”
Section: Pi3k In Innate and Adaptive Immunitymentioning
confidence: 99%
“…Further studies, including the suppression assay of Foxp3þ Tregs or the numbers of FoxP3þ Tregs in the spleen in our model, might be needed to explain this discrepancy. 27,[29][30][31] In conclusion, we have demonstrated that BG is capable of stimulating IL-10-producing CD4þ T cells, and suppressing the Th2 response in draining LNs and conjunctival eosinophil infiltration, demonstrating the therapeutic potential of topical BG for AC. Although further studies are required to understand the basis of the findings, our results should add new insight into the therapeutic potential of BG for allergic diseases including asthma or atopic dermatitis.…”
Section: Discussionmentioning
confidence: 95%